Determination of Activation Energy For Static Re-Crystallization in Nb- Ti Low Carbon Micro Alloyed Steel (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Data required for calculation the static re-crystallization kinetics have been evaluated from laboratory simulations. Series of two hit isothermal tests were conducted on high temperature torsion machine. These tests were conducted on four different temperatures and using inter-pass times between 0.5 and 5s with aim to investigate the influence of thermal activation on static re-crystallization. All tests were conducted on temperatures over TNR temperature, i.e. in temperature range in which all niobium is present only in solid solution. Method of evaluation of re-crystallization fraction was mechanical metallography, i.e. evaluation based on shape of each stress- strain curve. The fraction softening was calculated for all temperatures, together with avrami exponent, nA, and activation energy for re-crystallization, QSRX. Activation energy for static re-crystallization QSRX  281 KJ/mol and avrami exponent nA  1 determined in this work are in excellent agreement with previously reported data.